Understanding economics - Sobel, Russell S. 1968-; Gwartney, James D.; Stroup, Richard; Macpherson, David A. 1960- (South-Western, Cengage Learning, 2013)
Reflects economic conditions, enabling students to apply economic concepts to the world around them. This text includes analysis and explanation of measures of economic activity in the market. It also includes highlights of the recession of 2008-2009, and looks at the lives and contributions of notable economists.